A didactic guide of the text book, english for me to improve the english learning process in the "Emilio Abad" primary school - Pesantez Lozano, Jenny
This investigation is a didactic guide to improve the English teaching-learning process of the ?Emilio Abad? primary school. It primarily consists in designing and adapting games to be used together with the textbook English for Me. The theoretical background used to design the games encompasses ideas from the Natural and Communicative Approaches. The research started with a survey to disclosure the real situation of the teaching of English at that institution and finished with a description of 25 games and the ways they can be used (or adapted) to fit the needs of any English teacher working with children.